KONTRIBUSI KOMPETENSI MANAJERIAL KEPALA SEKOLAH TERHADAP MOTIVASI KERJA GURU SMP NEGERI DI KECAMATAN PADANG TIMUR - Silfianti (Universitas Negeri Padang, 2013)
This study aims to determine whether the principal managerial competencies contribute to teachers work motivation at SMP Negeri in East Padang District. Population of this research is all of employers 273 persons and 56 persons as a sample. The technique used Stratified Proportional Random Sampling. The tool to collect the data is questioner Likert scale models. Data were analyzed using product moment correlation formula, Test-r, t and t-test to see the contribution of KP. Results of data analysis showed that the motivation of the teachers are rather high category (79.71%), managerial competence principals are less able to the category (79.93%), and there is a contribution to the principal managerial competence motivation of teachers among 12, 18% in 95%. Kata Kunci; kompetensi manajerial, motivasi kerja